Berlin/London: London/Berlin — Cultural Transfer, Musical Theatre and the 'Cosmopolitan', 1890–1914. Issue 1 (May 2013) - Platt, Len; Becker, Tobias
During the period 1890–1914, a highly developed system of cultural transfer saw musicals being exchanged on a global scale. Traffic was continental - between such sites as London, Paris, Vienna, Berlin and Budapest - transatlantic and across the Empire. This essay focuses on one of the least explored legs of the network, London/Berlin. The aims are to contribute to contemporary debates about cosmopolitanism and its relations with formations of modernism, to shed light on how the culture industry was formulated at this early period and to examine relations between Britain and Germany in the 'Age of Empire', usually viewed in terms of an essential and almost unbridgeable Anglo-German antagonism, but which, against a more everyday reality, were considerably more ambiguous and nuanced.